2020
DOI: 10.1038/s41420-020-00326-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitidine chloride possesses anticancer property in lung cancer cells through activating Hippo signaling pathway

Abstract: Nitidine chloride (NC) has significant anti-tumor properties; however, the precise mechanism related to NC still needs further investigation. This study intends to investigate the anti-tumor functions and the feasible molecular basis of NC in NSCLC cells. Therefore, we determined the mechanism of NC-mediated anti-tumor function through various methods. Cell proliferation ability and migration and invasion were detected by CCK-8, colony formation assay and Transwell assay, respectively. Furthermore, flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In brief, the cells were seeded in a 96-well plate and transfected with plasmids for 4 h, and then the culture media were replaced and cultured for an additional 24 or 48 h. A 10 μL CCK-8 reagent was added to each well and incubated at 37 °C for 2 h. The absorbance at OD450 was detected by the Multiskan™ FC Microplate Photometer (Thermo Fisher). The transwell assays were conducted as previously reported [ 34 ]. The upper chamber was pre-treated with Matrigel matrix (#354230, BD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the cells were seeded in a 96-well plate and transfected with plasmids for 4 h, and then the culture media were replaced and cultured for an additional 24 or 48 h. A 10 μL CCK-8 reagent was added to each well and incubated at 37 °C for 2 h. The absorbance at OD450 was detected by the Multiskan™ FC Microplate Photometer (Thermo Fisher). The transwell assays were conducted as previously reported [ 34 ]. The upper chamber was pre-treated with Matrigel matrix (#354230, BD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This natural bioactive alkaloid is capable of inhibiting the malignant behavior of GBM through suppression of EMT and stem cell-like properties by modulation of the JAK2/STAT3 signaling pathway [209] and through targeting of PI3K/AKT/mTOR signaling pathway [210]. Lately, NC has been reported to have anticancer properties by activating the Hippo pathway in lungs cancer cells [211], thereby could be interesting to further investigate if NC may have a role in the activation of the Hippo signaling even in glioma cells (Table 3).…”
Section: Hippo Pathway and Glioblastoma: Pharmacological Interventionsmentioning
confidence: 99%
“…Natural compounds are an abundant source for the discovery of anti-cancer agents such as vincristine, vinblastine, paclitaxel, curcumin, colchicine and lycopene [28,29]. Lots of studies has reported NC exerted good efficacies for a variety of cancer by inducing apoptosis and autophagy [14,15,30]. In the present study, we observed that pretreatment with the apoptosis inhibitor (Z-VAD-FMK) or pyroptosis inhibitor (DSF) partly increased the cell viability after NC treatment rather than IM-54, nec-1, or fer-1.…”
Section: Discussionmentioning
confidence: 99%